AB0362 HIGH UNMET NEED AMONG RHEUMATOID ARTHRITIS PATIENTS WITH INADEQUATE RESPONSE TO BIOLOGIC DMARD: REAL-WORLD ANALYSIS OF 2012–2016 US MEDICARE DATA. (June 2019) - Dore, Robin K.; Antonova, Jenya; Guo, Haifeng; Suying, LI; Ozbay, Burak; Genovese, Mark C.
Abstract : Background: Within treat-to-target approach, ACR recommends biologic DMARD (bDMARD), with or without methotrexate, in rheumatoid arthritis (RA) patients whose disease is active despite methotrexate treatment 1 . ACR further defines bDMARD failure as the lack of efficacy (desired response) or side effects. Understanding the real-world characteristics and treatment patterns of the patients who become bDMARD inadequate responders (IR) may help clinicians tailor the next treatment to patient needs and health status. Objectives: This study described treatment patterns, treatment duration, and characteristics of RA patients who became IR to their first bDMARD. Methods: The study population included adult patients with Medicare medical and pharmacy insurance coverage (20% sample) who became bDMARD IR: ≥2 RA claims, newly initiated bDMARD (initial therapy) and then switched (index date) to another bDMARD or JAKi (index therapy). Patients with cancer, non-RA autoimmune disease, or pregnancy were excluded. At least 1 year pre- (baseline) and 1-year post-index enrollment was required. Patient characteristics and treatment allocation and duration were assessed. Results: A total of 528 bDMARD IR patients met the study selection criteria. At baseline, these patients used monotherapy (n=165, 31.2%) or bDMARD+csDMARD combination (n=363, 68.8%). Patient baseline demographics were comparable between monotherapy and combination therapy groups: mean (SD) age 65.6 (11.0) years, 82.0% female, 81.6% white. The mean (SD) Charleson Comorbidity Index was 1.8 (1.1) for monotherapy and 1.6 (1.0) for combination therapy (P=0.084). On average, patients used 14.8 (7.1) concomitant medications (comparable between groups). The original bDMARD treatment lasted for median 211 days, including 211 days for monotherapy and 212 days for combination therapy. As bDMARD IR patients switched treatment regimen, they started using either monotherapy (n=187, 35.4%) or combination therapy (n=341, 64.6%). The median duration of subsequent therapies was 287 days overall, including 224 days for monotherapy and 319 days for combination therapy (P=0.0063). Conclusion: Among Medicare bDMARD IR patients, the median duration of the initial bDMARD therapy lasted for 212 days or less and the subsequent treatments lasted for 319 days or less. This analysis suggests that bDMARD IR patients require alternative efficacious and well-tolerated treatments. References: [1] 2015 American College of Rheumatology Guideline for the Treatment of Rheumatoid Arthritis. Arthritis Care & Research DOI 10.1002/acr.22783 V C 2015, American College of Rheumatology Disclosure of Interests: Robin K Dore Grant/research support from: Gilead Sciences, AbbVie, Amgen, Lilly, Pfizer, Regeneron, Sanofi, Consultant for: AbbVie, Amgen, Lilly, Speakers bureau: AbbVie, Amgen, Lilly, Sanofi, Regeneron, Pfizer, UCB, Jenya Antonova Shareholder of: Gilead Sciences, Employee of: Eli Lilly and Company, Medimmune, Genentech, Gilead Sciences, Haifeng Guo: None declared, Suying Li: None declared, Burak Ozbay Shareholder of: Gilead Sciences, Employee of: Abbott Laboratories, Abbvie, Mark C. Genovese Grant/research support from: Sanofi/Genzyme, Genentech/Roche, RPharm, Consultant for: Sanofi/Genzyme, Genentech/Roche, RPharm